A HIGH RESOLUTION STUDY OF THE CHLOROPHYLL AND BACTERIOCHLOROPHYLL PIGMENT DISTRIBUTIONS IN A CALCITE/GYPSUM MICROBIAL MAT - Airs R.L.; Keely B.J. (My University, 2003)
Application of a high resolution high performance liquid chromatography-mass spectrometry method to the study of a microbial mat system has permitted the identification of a greater number of pigments derived from green bacteria than reported in a previous study. Although the green bacteria found in the mat were identified as Chloroflexus-like, bacteriochlorophylls and bacteriophaeophytins c that can be attributed to Chloroflexaceae on the basis of literature reports account for less than 10% of the pigments derived from green bacteria in the mat. Analysis of the bacteriochlorophylls and bacteriophaeophytins c and d using atmospheric pressure chemical ionisation-liquid chromatography-tandem mass spectrometry reveals complex depth profiles, signalling inputs from a number of organisms. The pigment compositions provide evidence for green bacteria living in close proximity to the living cyanobacterial mat. Depth profiles of pigments derived from green, purple and cyanobacteria indicate that the remnants of mats present in the deeper part of the section contain a record dominated by signatures from anoxygenic photoautotrophs.